The management of mucogingival defect after excision of a pyogenic granuloma: 3-year follow-up - Safa Ben Tanfous; Rym Masmoudi; Wiem Soudani; Leila Guezguez (Wolters Kluwer Medknow Publications, 2018)
The pyogenic granuloma (PG) is an exuberant tissue response to local irritation or trauma. The young lesions are highly vascular, red or reddish purple, often elevated and ulcerated, and bleed easily. Older lesions tend to be more collagenized and pink in appearance. Despite the name, no pyogenic material or pus is found in the lesion. Treatment protocol of PG includes many options. However, surgical excision is the treatment of choice. Several others highlighted the extremely varied recurrence rates. This case report aims to present 3-year follow-up management of mucogingival defect following surgical excision of PG.